Vasoactive intestinal peptide and cystic fibrosis transmembrane conductance regulator contribute to the transepithelial calcium transport across intestinal epithelium-like Caco-2 monolayer. - Mayuree Rodrat; Kannikar Wongdee; Jarinthorn Teerapornpuntakit; Jirawan Thongbunchoo; Duangrudee Tanramluk; Ratchaneevan Aeimlapa; Nithipak Thammayon; Natchayaporn Thonapan; Pathnaree Wattano; Narattaphol Charoenphandhu (PLoS ONE, 2022)
Vasoactive intestinal peptide (VIP) as a neurocrine factor released by enteric neurons has been postulated to participate in the regulation of transcellular active calcium transport across intestinal epithelium, but the preceding evidence is scant and inconclusive. Herein, transepithelial calcium flux and epithelial electrical parameters were determined by Ussing chamber technique with radioactive tracer in the intestinal epithelium-like Caco-2 monolayer grown on Snapwell. After 3-day culture, Caco-2 cells expressed mRNA of calcium transporters, i.e., TRPV6, calbindin-D9k, PMCA1b and NCX1, and exhibited transepithelial resistance of ~200 Ω cm2, a characteristic of leaky epithelium similar to the small intestine. VIP receptor agonist was able to enhance transcellular calcium flux, whereas VIP receptor antagonist totally abolished calcium fluxes induced by 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]. Since the intestinal cystic fibrosis transmembrane conductance regulator (CFTR) could be activated by VIP and calciotropic hormones, particularly parathyroid hormone, we sought to determine whether CFTR also contributed to the 1,25(OH)2D3-induced calcium transport. A selective CFTR inhibitor (20-200 μM CFTRinh-172) appeared to diminish calcium fluxes as well as transepithelial potential difference and short-circuit current, both of which indicated a decrease in electrogenic ion transport. On the other hand, 50 μM genistein-a molecule that could rapidly activate CFTR-was found to increase calcium transport. Our in silico molecular docking analysis confirmed direct binding of CFTRinh-172 and genistein to CFTR channels. In conclusion, VIP and CFTR apparently contributed to the intestinal calcium transport, especially in the presence of 1,25(OH)2D3, thereby supporting the existence of the neurocrine control of intestinal calcium absorption.